Impact of Point‐of‐care Testing on Length of Stay of Patients in the Emergency Department: A Cluster‐randomized Controlled Study. (27th July 2020) - Hausfater, Pierre; Hajage, David; Bulsei, Julie; Canavaggio, Pauline; Lafourcade, Alexandre; Paquet, Anne Laure; Arock, Michel; Durand‐Zaleski, Isabelle; Riou, Bruno; Oueidat, Nathalie
Abstract: Objectives: Crowding is a frequent concern in the emergency department (ED). Laboratory point‐of‐care testing (POCT) has been proposed to decrease patients' length of stay (LOS). Our objective was to determine whether an extended panel of POCT solutions could reduce LOS. Methods: This was a single‐center, prospective, open‐label, controlled cluster‐randomized study. Blood test processing was randomized into 1‐week inclusion periods: interventional arm (laboratory analyses performed on POCT analyzers implemented in the ED) or control arm (central laboratory). The primary endpoint was LOS of patients in the ED. Secondary endpoints were time to result (TTR), ED crowding surrogates, and average total cost of an ED visit in each arm. Results: A total of 23, 231 patients were included and 20, 923 were analyzed for the main outcome measure. Mean ± SD age was 46 ± 20 years, and 7, 905 (36%) underwent blood sampling. Mean ± SD LOSs were 203 ± 161 and 210 ± 168 minutes in the POCT and control arms, respectively. LOS reduction for the entire ED population was −9 minutes (95% confidence interval [CI] = −22 to 5, p = 0.22) compared to the control arm and −17 minutes (95% CI = −34.0 to 0.6, p = 0.06) for patients undergoing blood sampling. The mean ± SD TTRs were 28 ± 31 and 79 ± 34 minutes in the POCT and control arms, respectively (TTR reduction = −51 minutes, 95% CI = −54 to −48 minutes, p < 0.001). Conclusions: The implementation of an extended panel of POCT solutions in an ED did not significantly reduce the LOS, but reduced the TTR.